Windows 7 just the steps for dummies ebook - Muir, Nancy C. (Dummies., 2009)
Just the steps you need to get going with Windows 7! Coming in day and date with Microsoft's exciting release of the new Window 7 operating system, this friendly, accessible book shows you the features and functions you need from this exciting new operating system. Presented in a series of numbered steps that are concise, visually clear, and easy to follow, you'll learn to navigate the Windows 7 desktop, create files, connect to the Internet, search the Web, use e-mail, and more with this fun and practical guide. Get quickly and easily up to speed on Microsoft's new operating system, Windows 7 Master Windows 7 through a list of steps and easy-to-follow visual elements See how to set up your desktop, copy and delete files, connect to the Internet, create folders, and more Discover what so many readers already know-fun, readable Dummies books are a great way to get the most out of your Windows technology in a non-intimidating way Why waste time on extraneous information? Get this book and get just the steps!